Whatever Will Be Will Be: Queering Disabled Subjects’ Temporality - Sheldon, James; Rands, Kai (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2017)
Normative time is disciplined through what Freeman calls chrononormativity, and this disciplining is particularly evident in the experiences of disabled children. Despite the constant regimenting of the present reality for disabled children in time, they are essentially denied a future, the future generally being figured without people with disabilities. Exploring Muñoz’s critiques of Edelman, we emphasize the importance of futurity for children with disabilities, particularly one which they get to construct themselves rather than being constructed for them. We turn to Foucault’s discussion of the Ship of Fools in order to begin to imagine an alternative, queer time that is “steered” by children (and adults) with disabilities towards their own ends and goals.